Edaphic characterization of a forest savanna ecotone in southeastern Brazil - Ongaro Pinheiro, Marcelo H.; do Couto Moreno Arantes, Sayonara A.; Jimenez-Rueda, Jairo R. [UNESP]; Monteiro, Reinaldo [UNESP] (Fundação Zoobotanica Rio Grande Sul, Museu Ciencias Naturais, 2009)
Edaphic characterization of a forest savanna ecotone in southeastern Brazil. This study was motivated by the scarcity of studies involving descriptions of edaphic horizons in the transition from savanna to forest. It aims at comparing the chemical features and the texture of savanna and forest soils in one ecotone, and at considering possible edaphic influences on vegetation. In areas pertaining to the Botanical Garden of Bauru, State of São Paulo, two-meter deep pits were opened in different parts of a seasonal semi-deciduous forest and of a forested savanna to directly collect soil samples in different horizons. The physicochemical analysis revealed high contents of different nutrients, e.g., Ca and Mg, and low contents of Al in the superficial horizons of the seasonal forest, which were classified as eutrophic. Conversely, all the forested savanna horizons were considered as dystrophic. These edaphic features may be due to the different microenvironments of the studied phytocenoses.
Keywords: decomposition; organic matter; ground water; fire